Xeroradiography: Stagnated after a Promising Beginning? A Historical Review - Udoye, Christopher I; Jafarzadeh, Hamid (European Journal of Dentistry, 2010)
Various methods have been introduced for obtaining radiographs. Xeroradiography which is a method of imaging uses the xeroradiographic copying process to record images produced by diagnostic x-rays. It differs from halide film technique in that it involves neither wet chemical processing nor the use of dark room. Literature on this subject is scarce. After an initial promising beginning, this imaging method, once thought to hold the key to endodontic imaging, got stagnated. A revisit of this promising endodontic imaging system would therefore be appropriate. The purpose of this study was to review xeroradiographic technique as a roentgenographic imaging system. (Eur J Dent 2010;4:95-99)
Keywords: Endodontics; Radiography; Xeroradiography